2016
DOI: 10.1371/journal.pone.0150469
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Inducible Nitric Oxide Synthase by Lipopolysaccharide and the Influences of Cell Volume Changes, Stress Hormones and Oxidative Stress on Nitric Oxide Efflux from the Perfused Liver of Air-Breathing Catfish, Heteropneustes fossilis

Abstract: The air-breathing singhi catfish (Heteropneustes fossilis) is frequently being challenged by bacterial contaminants, and different environmental insults like osmotic, hyper-ammonia, dehydration and oxidative stresses in its natural habitats throughout the year. The main objectives of the present investigation were to determine (a) the possible induction of inducible nitric oxide synthase (iNOS) gene with enhanced production of nitric oxide (NO) by intra-peritoneal injection of lipopolysaccharide (LPS) (a bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Effects of microalgae on intestinal immunity is an area that has not been much exploited yet. However, Zahran and Risha (2014) have reported a positive effect of C. vulgaris on nitric oxide production, which is known to act as a mediator of different cell functions (Choudhury & Saha 2016). An enzyme responsible for nitric oxide synthesis, called inducible nitric oxide synthase (iNOS) is the key protein in intestinal immunity, as it controls inflammatory cytokines such as TNFa (Kousoulaki et al 2015).…”
Section: Chlorella Vulgaris In Fish and Crustaceans Immunitymentioning
confidence: 99%
“…Effects of microalgae on intestinal immunity is an area that has not been much exploited yet. However, Zahran and Risha (2014) have reported a positive effect of C. vulgaris on nitric oxide production, which is known to act as a mediator of different cell functions (Choudhury & Saha 2016). An enzyme responsible for nitric oxide synthesis, called inducible nitric oxide synthase (iNOS) is the key protein in intestinal immunity, as it controls inflammatory cytokines such as TNFa (Kousoulaki et al 2015).…”
Section: Chlorella Vulgaris In Fish and Crustaceans Immunitymentioning
confidence: 99%
“…he hepatoprotective potential of orally administered hydroethanolic seeds (HEBCS) in a rat induced acute liver injury is a wellestablished model to investigate the liver function atoprotective role of potential drug candidates. LPS induced hepatotoxicity is known to be associated with severe inflammatory responses and hepatic oxidative stress [34]. These are due to the involvement of the liver in the regulation of entry, metabolism, and clearance of LPS during exposure [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the hepatic and systemic toxicities exhibited by LPS have been due mainly to the release of pro-inflammatory cytokines, including TNF-α, IL-1β, and IL cytokines are produced following the binding of LPS to the CD14/LPS-binding protein and Toll like receptor-4 (TLR4) on the surface of Kupffer cells [36,37]. Subsequent interactions cause an increase in the expression of inducible enzymes/ proteins including COX-2, iNOS, and CRP an production of chemical oxidants such as superoxide radical anion ( Ÿ [34,38,39]. All these contribute to the hepatic injury in LPS -induced toxicity characterized by elevation of serum activities of ALP, AST, and ALT [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations